Two cases of neglected posterior fracture-dislocation of the shoulder with ipsilateral humeral shaft fracture - Micheloni, Gian Mario; Rebeccato, Arturo; Salmaso, Gianpaolo; Mazzi, Michele; Moscolo, Adriano; Giaretta, Stefano; Momoli, Alberto (Acta Biomedica Atenei Parmensis, 2019)
Posterior shoulder fracture-dislocations are rare. A combination of this injury with ipsilateral humeral shaft fracture is an extremely rare event. We report two cases of posterior shoulder fracture-dislocation with ipsilateral fracture shaft of humerus treated in our department. We highlight the rarity of the condition and the potential risk of recognize only the shaft fracture. We emphasize the importance of complete physical and radiological examination (x-rays and CT scan) in such cases to ensure early detection and its subsequent surgical treatment.